NEW TECHNIQUES FOR ADVANCING STUDENTS’ DIGITAL COMPETENCE - Jalgasbayev Sultanbek Tayrbek uli (Modern World Education: New Age Problems – New solutions, 2025)
The rapid expansion of digital technologies in education has positioned digital competence as a critical skill for students in higher education. This study examines innovative pedagogical approaches—gamification, project-based digital learning, and AI-supported tutoring—and evaluates their effectiveness in enhancing students’ digital skills. A mixed-methods research design was implemented among 120 university students over eight weeks. Quantitative results demonstrate a 27% increase in overall digital competence, with the highest gains observed in information literacy and creative digital production. Qualitative findings reveal improved motivation, collaboration, and confidence in digital environments. The study underscores the importance of integrating interactive and adaptive technologies into higher-education curricula to promote digital readiness.